Pengaruh Kewajaran Harga dan Kualitas Layanan Elektronik terhadap Niat Beli Ulang Netflix melalui Mediasi Citra Merek - Novriadi, Aang; Fiona, Febzi (Fakultas Ekonomi dan Bisnis Universitas Samudra, 2026)
This study examines how price fairness and e-service quality influence Netflix users' repurchase intentions, with brand image acting as a mediator. 180 respondents were selected as a sample using a non-probability method with a purposive sampling technique. The data analysis technique used SEM-PLS and was run through the SmartPLS version 4 program. The results indicate a direct relationship between price fairness and repurchase intentions, e-service quality and repurchase intentions, and brand image and repurchase intentions, all of which show a significant positive influence. Meanwhile, the indirect influence mediated by brand image, both the path from price fairness through brand image to repurchase intentions, and from e-service quality through brand image to repurchase intentions, also proved to have a positive and significant influence.